Evaluation of no evidence of progression or active disease (nepad) in patients with primary progressive multiple sclerosis in the oratorio trial. Issue 5 (8th May 2017) - Wolinsky, Jerry; Montalban, Xavier; Kappos, Ludwig; Hauser, Stephen; Giovannoni, Gavin; Seze, Jerome de; Bar-Or, Amit; Masterman, Donna; Bernasconi, Corrado; Wei, Wei; Garren, Hideki; Chin, Peter; et al.
Abstract : Objectives: To assess the effect of ocrelizumab from baseline to Week 120 on the proportion of patients with no evidence of progression or active disease (NEPAD) in the Phase III, placebo-controlled ORATORIO study in primary progressive multiple sclerosis (PPMS). PPMS is characterised by steadily increasing neurologic disability. The analysis of accompanying inflammatory disease activity in PPMS, including brain MRI activity and relapses, has to date been limited. NEPAD is a novel composite endpoint that assesses the combined absence of disease progression and active disease in patients with PPMS. Methods: In a post-hoc exploratory analysis of the ORATORIO trial, 234 placebo- and 465 ocrelizumab-treated patients were evaluated to assess the proportion of patients with NEPAD, defined as having no evidence of progression (no 12 weeks confirmed progression of ≥1/≥0.5 points on the Expanded Disability Status Scale if the baseline score was ≤5.5/>5.5 points, respectively; no 12 weeks confirmed progression of ≥20% on the timed 25 foot walk test and 9-hole peg test), no brain MRI activity (no new/enlarging T2 lesions and no T1 Gd + lesions), and no protocol-defined relapse. Brain MRI assessments were conducted at baseline and weeks 24, 48, and 120. Results: Compared with placebo, ocrelizumab increased the proportion of patients with NEPAD at Week 120 (9.4% vs 29.9%; risk ratio ocrelizumab vs placebo (95% CI): 3.15 (2.07 to 4.79); p<0.0001). A consistent effect of ocrelizumab was also observed on all three components of NEPAD. Sensitivity analyses will also be presented. Conclusions: In the ORATORIO trial, ocrelizumab increased by approximately 3-fold the proportion of patients with NEPAD vs placebo, as measured by the combination of no evidence of progression, no relapse and no MRI activity. NEPAD may represent a useful composite outcome to assess the absence of clinical and MRI features of disease progression and activity in patients with PPMS.